Long-tailed Macaques Macaca fascicularis (Simiiformes: Cercopithecidae) Coexistence with Settlements in the Nyaru Menteng Arboretum Area, Central Kalimantan - Hasanah, Rizka; Purnaningsih, Titin; Anggoro, Rahayu Opi; Decenly; Syafutra, Randy (BIO PALEMBANICA, 2025)
The Nyaru Menteng Arboretum area in Central Kalimantan serves as a habitat for approximately 200 Long-Tailed Macaques Macaca fascicularis within its 65.2-hectare area, as recorded in 2024. A lack of food causes presumed M. fascicularis to descend to settlements in search of food, resulting in losses for the people of Nyaru Menteng Arboretum which leads to coexistence. This study aims to identify the types of coexistences that occur between M. fascicularis and villagers. The method used to identify coexistences is a survey method. The survey results explain that the types of coexistences that occur range from stealing side dishes (25%), damaging ceilings (25%) and messing up the kitchen (50%). Human resistance in the form of repellent using slingshots 32%, wood 40%, nets 20% and air rifles 8%. The findings of this study can serve as a reference for managing future coexistences and inform decision-making for effective M. fascicularis management in the Menteng Arboretum Area, Central Kalimantan.   Keywords: Endangered, Indonesian Borneo, interaction, Long-Tailed Monkey, Macaca fascicularis.